Quality Leadership Style as an Approach to School Performance: Strategy and Management - Abdurrahman, Faizar; Ilham, Muhammad (Al Mabhats : Jurnal Penelitian Sosial Agama, 2022)
Abstract: This research uses a quantitative research paradigm and a survey method. It aims to determine the influence of strategic management and transformational leadership on school quality. The technique used in this research is the total sampling technique, taking the entire population to be studied. The results of this study show that there is a significant influence of (1) strategic management on school quality based on the level of significance (Sig = 0.000) and a correlation coefficient value of 6.14 > 1.68, which is 46%; (2) transformational leadership on school quality with a correlation coefficient value of 4.14 > 1.68, which is 28%; (3) strategic management and transformational leadership simultaneously influence school quality with a correlation coefficient of 18.854 > 3.20, which is 47%. Therefore, the test results indicate a direct influence of strategic management and transformational leadership on school quality. Abstrak: Penelitian ini menggunakan paradigma penelitian kuantitatif metode survey. Bertujuan untuk mengetahui besaran pengaruh manajemen strategi dan kepemimpinan transformasional terhadap mutu sekolah. Teknik yang digunakan dalam penelitian ini adalah Teknik total sampling dengan mengambil seluruh populasi untuk diteliti. Hasil dari pengujian ini menyatakan bahwa terdapat: (1) pengaruh manajemen strategi terhadap mutu sekolah adalah signifikan, berlandaskan pada tingkat signifikasi (Sig = 0,000) dan nilai koefisensi kolerasi sebesar 6,14 > 1,68 yaitu 46%; (2) pengaruh kepemimpinan transformasional terhadap mutu sekolah dengan nilai koefisiensi korelasi 4,14>1,68 yaitu 28%; (3) manajemen strategi dan kepemimpinan transformasional secara simultan berpengaruh terhadap mutu sekolah dengan koefisiensi korelasi 18,854 > 3,20 yaitu 47%. Dengan demikian hasil uji ini menyatakan bahwa terdapat pengaruh langsung manajemen strategi dan kepemimpinan transformasional terhdap mutu sekolah.